Analyzing Social Media Tourism Content for Content Creation on Wang Krod Community’s Social Media Platforms - Chumnumwat, Songpol; Chanvichai, Kittima (Journal of Business, Innovation and Sustainability (JBIS), 2026)
This research aims to study the characteristics of content used for communication on social media platforms in the tourism sector and to apply the characteristics of the studied content to content creation for Wang Krod community. The objective is to analyze the characteristics of digital content used for tourism promotion on social media platforms. The sample group used in studying the characteristics of digital content related to tourism consists of the first 10 social media user accounts that present tourism content and have more than 1,000,000 followers on social media platforms. The selection of content for analysis was based on a conceptual framework, with the criteria that the content must have been published between 2021 and 2023 and must not be direct advertisements of products or services. The research instrument is a content collection form. The analyzed data were categorized, summarized, and interpreted using an inductive approach, with findings discussed in relation to relevant theories. The research findings reveal that tourism-related social media content is mainly presented in the forms of entertainment and inspiration. Such content emphasizes emotions, personal travel experiences, and storytelling, often using casual language, humor, and narrative structures. High-quality photographs and videos play a crucial role in enhancing visual appeal and audience attention. The study also identifies a systematic process for creating tourism content on social media, including community SWOT analysis, selection of cultural elements, determination of content formats and categories, storytelling design, content verification, publication, and performance evaluation. This process enables communities to plan content more strategically and communicate tourism information throughout the year, while also fostering audience engagement through interactive activities. The discussion highlights that while entertain and inspire content are effective in attracting attention and raising travel interest, overreliance on such content may risk oversimplifying community identity. In culturally diverse communities, greater emphasis on educational content is necessary to support sustainable tourism communication. In addition, the findings indicate that limited digital skills within communities remain a key challenge, suggesting the need for policy-level support to enhance digital communication capacity and reduce long-term competitive in tourism promotion.